Effects of Zn content on the magnetic and magnetocaloric properties of Ni-Zn fenites - Chau, N; Thuan, N K; Minh, D L; Luong, N H (VNU Journal of Science: Mathematics - Physics; Vol 24 No 3, 2008)
Abstract